KONSEKUENSI PEMBELAJARAN TEMATIK DI TK DAN SD - Adi, Waluyo (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Consequence in tematic study application has not optimal in early age education either in kindergarten and initial class of elementary school less optimal of planning, execution and valuation. To maximize the education hence the executors claimed to comprehend the conception and actual condition. By comprehending the current underlying principles of tematic education and tematic education characteristic, then all this things can be practiced by forming plan and practiced in integral and holistic execution with intact assessment.